Computational science and its applications – ICCSA 2019 : 19th International Conference, Saint Petersburg, Russia, July 1-4, 2019, Proceedings.: 19th International Conference, Saint Petersburg, Russia, July 1-4, 2019, Proceedings. Part III (2019) - Unknown
No abstract available